Game Edukasi:Apakah Efektif ? - Nisa Fitriani (Fakultas Dakwah UIN KHAS Jember, 2025)
This study explores the effectiveness of educational games as an innovative medium to enhance students' learning outcomes, focusing on cognitive abilities, learning motivation, and social skills. The scope of this research includes analyzing the short- and long-term impacts of educational games on elementary and secondary education levels. Utilizing library research, the study examines articles, books, and research reports from the last decade. Data were analyzed using thematic analysis to identify key themes surrounding the benefits and limitations of educational games. The findings reveal that educational games significantly enhance cognitive skills, especially in problem-solving and critical thinking. Games also boost learning motivation through interactive and engaging content, providing instant feedback and progressive challenges. Furthermore, collaborative educational games improve social skills, including communication and teamwork. However, excessive screen time poses potential drawbacks, emphasizing the importance of balanced game usage. This research concludes that educational games are effective as supplementary tools in learning but require careful integration into educational practices to maximize their potential benefits.